What we need for a sustainable industrialization of Peru? A proposal of the industrial model - Porlles Loarte, José (2015)
Several experts were predicting the end of the cycle of prosperity based on the exploitation of raw materials, especially minerals. Peru has beenaffected by this situation highlighting once again that the current primary export model does not provide a sustainable development in the long term. In this context of a slowdown in our economy, we believe that the industrialization of our resources is the most advantageous alternative to be undertaken by the country. In this respect, the present work is a contribution of ideas to promote a change of the industrial model should have the Peru, for which, in the analysis has taken into account various documents and related entities recognized these issues.